2013
DOI: 10.1088/0268-1242/28/6/065005
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous two-color lasing in a single CdSSe heterostructure nanosheet

Abstract: Abstract:The ability of a single monolithic semiconductor structure to emit or lase in a broad spectrum range is of great importance for many applications such as solid state lighting and multi-spectrum detection. But spectral range of a laser or light emitting diode made of a given semiconductor is typically limited by its emission or gain bandwidth. Due to lattice mismatch, it is typically difficult to grow thin film or bulk materials with very different bandgaps in a monolithic fashion. But nanomaterials su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
33
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 31 publications
(33 citation statements)
references
References 43 publications
0
33
0
Order By: Relevance
“…MSHNs are otherwise grown as freestanding structures without epitaxial connection with the substrate, because the original growth substrates can be amorphous or non-lattice-matched crystals. The overall set-up and VLS growth mechanism are described in several earlier papers 24,33,48 and are shown schematically in Fig. 1a.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…MSHNs are otherwise grown as freestanding structures without epitaxial connection with the substrate, because the original growth substrates can be amorphous or non-lattice-matched crystals. The overall set-up and VLS growth mechanism are described in several earlier papers 24,33,48 and are shown schematically in Fig. 1a.…”
Section: Methodsmentioning
confidence: 99%
“…lumenera.com/). Due to the large size of the nanosheet structures, different longitudinal and transverse modes cause very close mode spacing 24 , so more modes are excited above the threshold with increasing pumping intensity. At a pumping level of 3.9 μJ, multimode lasing can be clearly observed.…”
Section: Multi-colour Lasingmentioning
confidence: 99%
See 1 more Smart Citation
“…Complete compositional variation in single nanostructures is a critical step in the process of attaining wide‐range wavelength tunability. These innovative chemical growth techniques have boosted the development of white‐light emission, multiwavelength MNLs, and wavelength‐tunable MNLs …”
Section: Bandgap Tuning For Wavelength‐tunable Mnlsmentioning
confidence: 99%
“…Such procedures to remove LEDs from the original growth substrates and mounting to new common platform significantly increase the complexity and the cost of fabrication . This is why over the last several years significant efforts have been devoted to the growth of different materials on a given substrate utilizing the unique properties of nanoscale materials and growth techniques . It has been shown that wide coverage of the visible spectrum, from UV to IR, can be achieved with nanostructures grown on a single substrate using a single growth run .…”
Section: Introductionmentioning
confidence: 99%